Poslovna statistika - Tominc , Polona; Rožman, Maja (University of Maribor Press, 2023)
Business Statistics. The course Business Statistics, for which this collection of exercises/tutorials is intended, is important for students to develop the ability to understand the information in data. These tutorials contain the following chapters: data visualisation using tables and graphs, relative numbers, measures of central tendency, measures of dispersion, skewness and kurtosis, confidence intervals for statistical parameters and the basis of hypothesis testing of statistical parameters, basics of simple regression and basics of time series analysis and forecasting.